Upaya Peningkatan Pelayanan Administrasi Kependudukan Melalui Klampid New Generation (KNG) di Kelurahan Kebraon Kota Surabaya - Gultom, Iin Yusniar Alvianda Ningrum; Prastyawan , Agus (Universitas Negeri Surabaya, 2023)
Modernization is a complete change from a traditional society to a more advanced society. Indonesia is implementing modernization, especially in public services such as population administration. One of the solutions offered is a web-based population administration service (online). This is a breakthrough to increase public satisfaction with government performance as well as to optimize information and communication technology. By utilizing this technology, people can be served quickly and easily, anytime and anywhere. The results of this study indicate that the increase in Population Administration Services through Klampid New Generation (KNG) in the Kebraon Village, Surabaya City is measured using Service Standard indicators according to the Minister of State Administrative and Bureaucratic Reform Regulation No. 15 of 2014 concerning Service Standard Guidelines. The preparation, determination and application of Service Standards is carried out by taking into account the following principles: (1) Simple, considered inappropriate because it still has convoluted problems. (2) Participatory, considered appropriate in providing solutions, education, and outreach to the community. (3) Accountable, considered not meeting accountability standards due to lack of information on the requirements provided to the community, but the service is in accordance with SOP and on time. (4) Sustainable, considered sufficient to meet community expectations and services available at the RW hall. (5) Transparency, considered to be sufficiently transparent to the public even though some elderly people have difficulties with technology. (6) Justice, considered appropriate in providing services to the community without discriminating, all receive the same treatment. Conclusions regarding Population Administration Services Through Klampid New Generation (KNG) can be considered good in providing population administration services to the community. It is in accordance with the SOP that has been set, the service is also on time, there is no discrimination and in accordance with service standards. Keywords: Population Administration, Public Service, Klampid New Generation (KNG)